Greckie nazwy dużych zwierząt morskich w świetle relacji Eliana (O naturze zwierząt IX 49) - Kaczyńska, Elwira; Witczak, Krzysztof Tomasz (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
The paper analyzes chapter IX 49 of Aelian’s De natura animalium, devoted to the largest sea animals. It is accompanied by a Polish translation and appropriate comments. Aelian provides numerous Ancient Greek names for large sharks and sea mammals, including the “sea lion,” hammer-headed shark, “sea leopard”, whales, sawfish, malthe, “sea ram”, “sea hyena” and “sea dogs”. The names are explained from the point of view of semantic motivation; some new identifications of sea monsters are suggested as well.